The influence of lime type on the properties of traditional lime-soil materials - Shiqiang Fang; Wenjing Hu; Xueqiang Chen; Lina Xie; Luxiang Cai (PLoS ONE, 2026)
The conservation of historic earthen structures requires repair materials that are both high-performance and historically appropriate. While archaeological evidence indicates that the historical use of blocky quicklime to make lime-soil materials, modern research and conservation practice often focus on its powdered counterpart, creating a knowledge gap. Thus, this work systematically evaluated the physical properties, microstructure, and composition of lime-soil materials prepared with blocky quicklime, powdered quicklime, and hydrated lime (at 10–20% content). The results demonstrated that hydrated lime yielded inferior strength and durability. Although both types of quicklime enhanced performance, they functioned through distinct mechanisms. Powdered quicklime provided consistent, dosage-dependent improvement, making it reliable for high-performance requirements. In contrast, blocky quicklime exhibited a pronounced optimum at 15% content; beyond this, performance declined due to expansion stresses from excess, partially hydrated cores, as identified by FT-IR spectroscopy. This study concluded that the choice of lime form was critical: powdered quicklime was recommended for predictable, broad-spectrum enhancement, whereas blocky quicklime could be effective but required strict dosage control to harness its unique potential and avoid damage. These findings provided a scientific basis for selecting and applying lime materials in the repair of earthen architectural heritage.